The effects of intrinsic and extrinsic motivation on turnover intention among employees in the Malaysian banking industry: Job satisfaction as a mediator - Sujatha, Anbalagan (2023)
Turnover rate of bank employees should not be neglected as the employees are the important assets of Malaysia’s growth in regards of financial system. Current research is particularly conducted among the Malaysian banking industry as their turnover rates are high as compared to other sectors. Plus, previous studies had addressed that bank employees are less in both motivation and job satisfaction. Most of the studies focus on determining the relationship between motivations and turnover intention but this study would provide a better understanding on different types of motivation (intrinsic and extrinsic) that can lead to turnover intention by using job satisfaction as a mediating variable. This study applied a cross-sectional design and used online survey method in data collection. This study collected 400 responses from bank employees age between 25 to 60 years old with the purposive sampling. Questionnaires included “Intrinsic Motivation Scale” Ewen et al. (1966), “Extrinsic Motivation Scale” Ewen et al. (1966), “Job Satisfaction Scale” Agho et al. (1993) and “Turnover Intention Scale (TIS)” Dysvik and Kuvaas (2010) were used. Current study showed that there is a significant negative relationship between iii motivation (intrinsic and extrinsic) and turnover intention. Further, revealed that there is a significant positive relationship between motivation (intrinsic and extrinsic) and job satisfaction. Plus, showed there is a significant negative relationship between job satisfaction and turnover intention among bank employees in Malaysia. Plus, PROCESS macro was used to study on the mediating effect where the finding illustrates that job satisfaction complementary mediated the relationship between motivation (intrinsic and extrinsic) and turnover intention among employees in Malaysian banking industry. Herzberg's Motivator and Hygiene theory sheds light on the essential components that motivate workers. It can be used to understand each employee's motivation and level of job satisfaction, which can then be applied to create an all-encompassing employee retention strategy. Findings of this research are expected to be beneficial to the managing body of the bank managers and human resources division to create a satisfied workforce plus to evolve a motivating condition which would help reduce in turnover intention among bank employees.